Fabrication of PLA-PEG Nanoparticles as Delivery Systems for Improved Stability and Controlled Release of Catechin. (14th September 2017) - Singh, Neha Atulkumar; Mandal, Abul Kalam Azad; Khan, Zaved Ahmed
Abstract : The purpose of this study was to develop an oral delivery system for the controlled release of catechin and evaluate the antioxidant potential and stability of catechin loaded PLA/PEG nanoparticles (CATNP). Nanoparticles were synthesized using a double emulsion solvent evaporation method. The fabricated nanoparticles were relatively small with a hydrodynamic diameter of 300 nm and an encapsulation efficiency of 95%. SEM image analysis showed uniform sized and spherically shaped nanoparticles. In vitro release profiles indicated a slow and sustained release of catechin from the nanoparticle. Stability of the nanoparticle in simulated gastric and intestinal fluids is maintained due to the PEG coating on the nanoparticles, which effectively protected catechin against gastrointestinal enzyme activity. Enhanced inhibition action of free radicals and metal chelation potential was noted when catechin was encapsulated in these polymeric nanoparticles. The reports obtained from this study would provide an opportunity for designing an oral delivery system aimed at inhibiting oxidative stress in the human body.